Effects of static magnetic fields on onion (Allium cepa L.) seed germination and early seedling growth - Morillo-Coronado, Ana Cruz; Martínez-Anzola, Herlyn Giovanni; Velandia-Díaz, Julián David; Morillo-Coronado, Yacenia (Revista de Ciencias Agrícolas, 2021)
In vegetables of economic importance such as onion, one of the main limitations in their production is that their seeds have a relatively short storage life, so their viability decreases rapidly. Research has been carried out on onions to improve seed germination and to extend its use for sowing. The magnetic field is considered a simple, inexpensive, and non-invasive physical method to stimulate the germination process, compared to traditional chemical methods. In this sense the objective of this research were to evaluate the effects of static magnetic fields on Yellow Granex PRR hybrid onion (Allium cepa L.) seed germination, and early growth in the laboratory conditions. Seeds were exposed to 10 and 21mT, (mT=militesla), static magnetic fields induced by magnets for 0, 5, 3, 6, 12 and 24h; each treatment had four repetitions. The results showed that the low intensity stationary magnetic fields (10 and 21mT) did not cause significant differences in germination, dry weight, or fresh weight, but for the seedling length. It is necessary to increase the intensity of the magnetic fields and the exposure time to achieve important physiological changes that positively affect the germination and growth of onion seeds, and thus contribute to the improvement of their yield and productivity. The use of physical methods such as magnetism can stimulate different physiological processes in plants and thus contribute to the improvement of characteristics of agronomic interest.